Uncovering and elimination of the natural separation of interacting molecules of standard REBCO crystals, a panacea for improvement of its delamination strength. (January 2020) - Mbam, Stephen Ogbonna; Gou, Xiao-Fan
Highlights: Standard rare-earth barium copper oxide crystals were studied by Hamaker method. Intermolecular interactions of the crystals exhibit natural separation. Natural separation of the crystals introduces specific microstructural defects. The microstructural defects reduce the delamination strength of the crystals. The crystals require specific densifications to eliminate natural separation. Abstract: The intermolecular interactions characteristics for constituent molecules of standard rare-earth barium copper oxide (REBCO, rare-earth (RE) are gadolinium (Gd), samarium (Sm), and yttrium (Y)) coated conductor (CC) crystals was studied by Hamaker method. On the Hamaker model, we used the deductions for the combining laws of the Hamaker constants for the interacting molecules to uncover and eliminate the intermolecular interactions responsible for introducing specific microstructural defects in the REBCO crystals. The computed results showed that some molecules of the REBCO crystals could separate naturally due to dispersion forces only, thereby creating microstructural defects in the crystals. Under the given parameters, we found out that it is more beneficial to increase the Hamaker constant of the intervening medium, A 33 responsible for introducing the microstructural defects than decreasing it to obtain a REBCO crystal that would have robust delamination strength. For instance, by increasing the A 33 from 25 × 10 - 20 J to 30 × 10 - 20 J (i.e., only 0.2%), it corresponds to the improvement of the delamination strength of the bulk REBCO crystals from approximately 95 MPa to 106 MPa (0.12%). The computed results agree reasonably well with the Hamaker constants of similar ceramic oxides and REBCO's delamination strength found in the literature, which is 9.01 - 10.20 × 10 - 20 J and 10–100 MPa respectively.